(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The utilization of 3D printers in small businesses has revolutionized manufacturing processes, offering cost-effective and customizable solutions. This article explores the benefits, challenges, and practical applications of 3D printing technology in small-scale enterprises. 3D printing has the potential to impact numerous industries positively. Here are some ways businesses currently use 3D printing to meet their needs.